Evolução geomorfológica do sítio natural de Fortaleza, Ceará - Moura Fé, Marcelo Martins de (2008)
The natural site of Fortaleza city, despite of the present standards of use and occupation of the soil, still presents a significant natural diversity, which were approached in this work under a geomorphological analysis that is initiated in the geological long term and achieves in the present days. The objectives ot the work are the main aspects of the geomorphological genesis and evolution of the natural site of the city of Fortaleza, capital of the State of Ceará, Northeast of Brazil, having as theoretical support the Principle of Actualism, associated to an assembly of techniques that permitted the development of the analyses about the subject researched. The work, divided in three part, besides presenting a natural characterization of the city of Fortaleza, highlights the main elements of the morphostructural evolution of the area during the Cretaceous, the Quaternary and Tertiary periods and its inherent events. Regarding the most recent aspects of the geomorphological evolution, we discuss the present reliefs of the natural site of Fortaleza, with characterizations and vertical analyses, as well as the role of these reliefs in the present dynamics. Finalizing the research, we analyze the main process of environmental degradation of the landscape associated to the more significant urban development of Fortaleza, as well as the consequences of the environmental degradation for the routine one of the city in the century XXI. The results obtained could indicated the geomorphological features resultant of the action of geomorphological process during the Cretaceous still presents in the landscape, as well as its influence in the subsequent geomorphological evolution. Besides, we present a hypothesis of evolution for the deposition of the Barreiras Formation during the Tertiary, as well as a proposal of a possible paleo-valley of Cocó River, the main river of the city, which would have been changed during the Quaternary until achieve its present characteristics. On the basis of the mapping carried out and analyzed, we also propose a classification for the ponds that caractherized the natural site of Fortaleza. Finally, we present the main morphological characteristics of the city, as well as the present situation of its relifs. Finalizing, we analyze the influence of the process of development in the degradation of those features, the factors and the effects of the pressure exercised by the society, the worry about the way this situation is developing, the need of thinking and rethinking these conditions, as well as the importance of the natural site of the city, not well known to their citizens, in its essence and dynamics.